Aging effect on the physical properties of polyurethane modified bitumen - Khairuddin, Faridah Hanim; Ibrahim, Ahmad Nazrul Hakimi; Rahmad, Suzielah; Md Yusoff, Nur Izzi; Badri, Khairiah; Misnon, Noor Aina; Ismail, Norfarah Nadia (Science Publishing Corporation Inc., 2018)
One of the ways oxidation affect pavement properties is through the aging of bitumen. The aim of this research is to evaluate the effects of aging on 60/70 penetration grade bitumen modified with polyurethane (PU). The unmodified and modified bitumen were artificially aged using the rolling thin film oven (RTFO) and pressure aging vessel (PAV) methods to simulate short term aging (STA) and long-term aging (LTA), respectively. Effects of aging were evaluated by performing consistency tests namely penetration, softening point, viscosity tests at 135°C, and through aging index. The results of these tests shows that adding 3% PU to the bitumen decreases the penetration value while at the same time increasing its softening point in comparison to base bitumen (B-B). A very high increase in viscosity was observed due to the hardening effect of PU. The computed aging index (AI) shows that PU reduces aging effects on the physical properties of the bitumen as indicated by the lower aging index value of the penetration, softening point, and viscosity tests subsequent to aging. The addition of PU clearly results in improved bitumen resistance to oxidative aging. Morphology observation shows that no separation occurs in the polyurethane modified bitumen (B-PU) and that the sample was homogeneously blended and uniformly dispersed during the mixing process.